2018
DOI: 10.20960/nh.1843
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and adequacy in Mexican preschool children: National Health and Nutrition Survey 2012

Abstract: Objective: to estimate energy, nutrient intake and diet adequacy in preschool-aged children based on data from the Mexican National Health and Nutrition Survey 2012.Material and methods: dietary data in children < 5 years (n = 1,212) collected through a Semi-quantitative Food Frequency Questionnaire (SFFQ) were analyzed. Energy and daily nutrient intakes and adequacies were calculated comparing by sociodemographic characteristics.Results: median daily energy intake was 1,252 kcal (adequacy 104%). Adequacies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Calcium intake increased with age, as has been found in other studies [13,46]; but as the AR also increases with age, the percentage of children with <AR intakes was higher in the older groups, especially in those of 4 to <6 years (Table 2 and Supplementary Table S1).…”
Section: Calciumsupporting
confidence: 81%
See 2 more Smart Citations
“…Calcium intake increased with age, as has been found in other studies [13,46]; but as the AR also increases with age, the percentage of children with <AR intakes was higher in the older groups, especially in those of 4 to <6 years (Table 2 and Supplementary Table S1).…”
Section: Calciumsupporting
confidence: 81%
“…Among the nutrients studied, calcium and vitamin D have been the most frequently analyzed, in relation to bone mass [ 4 , 12 , 14 , 20 , 45 , 46 , 47 ]. However, it is also important to pay attention to magnesium in relation to children’s bone health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Brazilian study also confirmed the predictive importance of socio-economic factors on the development of indicators regarding nutritional status among children aged 0-3, with an indication of more favourable rates for children of mothers with higher socio-economic status [2]. Diversity in the nutritional value of the diet depending on living environment has been described among Mexican preschool children, with an indication of more favourable results among urban children than in rural areas [15]. Other Polish studies on diet structure and body mass index among preschool children in relation to place of residence showed differences in anthropometric indicators and diet structure depending on region (children from the western region of Poland had a significantly higher BMI than those from other regions) [36].…”
Section: 7% Energy)mentioning
confidence: 64%
“…The low frequency of consuming whole-grain cereal products has also been described among preschoolers from Białowieża county [43]. A low intake of wholemeal cereal products may generate a risk of fibre supply deficiencies in food rations, as confirmed by studies conducted in Lublin [22], and also Mexican kindergartens [15].…”
Section: Discussionmentioning
confidence: 85%